Pytanie prawne do Trybunału Sprawiedliwości Wspólnot Europejskich w sprawie karnej - Klejnowska, Monika (My University, 2015)
The paper has presented the procedure of addressing by a Polish court the Court of Justice of the European Communities with a question on a point of law in a criminal case and the course of proceedings before the Court, as well as the importance and consequences for criminal proceedings in an individual case of the Court’s decision, including interpretation of the community law in an answer to the put question on a point of law. At the same time the Author has raised the question of the Court’s cognition limits in connection with the cognition limits of a Polish criminal court sending such a question on a point of law, especially the limits set by the regulations of the domestic law, lying outside the scope of the European Community legislation. The considerations have shown an influence of the cognition range of a Polish criminal court on the Court’s cognition range in a specific criminal case, and whether and to what extent the Court must (answering a question on a point of law by a domestic court) consider trial standards restricted exclusively for the domestic legislator, and particularly those that grant trial guarantees to participants of a trial. This issue is important in the context of importance assessment of decisions by the Court of Justice of the European Communities for decisions made in the Polish criminal proceedings, especially in the context of endeavours for unification of court decisions in the member countries based on the EU law standards
QUESTION ON A POINT OF LAW TO COURT OF JUSTICE OF EUROPEAN COMMUNITIES IN CRIMINAL CASE